Cardio-sarcopenia: A syndrome of concern in aging - Loh, De Rong; Tan, Ru-San; Lim, Wee Shiong; Koh, Angela S. (Frontiers in Medicine, 2022)
Cardiac alterations in structure and function, namely, the left ventricle, have been intensely studied for decades, in association with aging. In recent times, there has been keen interest in describing myocardial changes that accompany skeletal muscle changes in older adults. Initially described as a cardio-sarcopenia syndrome where alterations in myocardial structure were observed particularly among older adults with skeletal muscle sarcopenia, investigations into this syndrome have spurred a fresh level of interest in the cardiac-skeletal muscle axis. The purpose of this perspective is to summarize the background for this ‘syndrome of concern’, review the body of work generated by various human aging cohorts, and to explore future directions and opportunities for understanding this syndrome.